COVID-19 in renal-transplanted recipients: a narrative review - Martins, Suellen Rodrigues; Alves, Lorraine Vieira; Corgozinho, Marta Lamounier Moura Vargas; Reis, Jenner Karlisson Pimenta dos; Mota, Bruno Eduardo Fernandes; Farah, Kátia de Paula; Gomes, Karina Braga; Dusse, Luci Maria Santana; Alpoim, Patrícia Nessralla; Mota, Ana Paula Lucas (Brazilian Journal of Transplantation, 2021)
COVID-19 is an emerging disease mainly associated with Severe Acute Respiratory Syndrome (SARS). This disease causes a cytokine storm release in response to viral infection, and can lead to several systemic complications. Acute kidney injury (AKI) is one of these complications and renal replacement therapy may be necessary for the infected patient. In this context, renal-transplanted recipients (RTR) and patients with chronic kidney diseases are in the risk groups for COVID-19 due to their increased inflammatory state and endothelial dysfunction. Furthermore, maintenance immunosuppressive therapy in RTR can also be another complicating factor, since it influences the response from the immune system against pathogens, including SARS-CoV-2. However, it is believed that the worst outcomes of COVID-19 are mainly caused by an exaggerated inflammatory response than to the direct virus action; therefore, in a hyper-inflammatory state, immunosuppression therapy could be beneficial. This narrative review aims to present the main clinical and laboratory findings of 22 studies involving RTR affected by COVID-19. This review can contribute to the management of COVID-19 and its consequences in this risk group.